A national multi-institutional analysis of predictors of surgical site complications and unplanned reoperation after paramedian forehead flap reconstruction,. (December 2022) - Ni, Garrett; Brebion, Rohan; Baltodano, Pablo A.; Coronado, Michael C.; Elmer, Nicholas; Webster, Theresa K.; Zhao, Huaqing; Lu, Xiaoning; Araya, Sthefano; Patel, Sameer
Abstract: Background: Although postoperative complications of paramedian forehead flap (PMFF) are generally low, surgical site complications and unplanned reoperation can still occur. Recent literature suggests infection to be the most common complication following PMFF reconstruction. This study sought to determine the patient and preoperative factors associated with surgical site complications and unplanned reoperations at a national level. Methods: Patients who underwent PMFF reconstruction from the ACS-NSQIP 2007 – 2019 database were analyzed to determine composite surgical site morbidity and unplanned return to the operating room. Patient and operative factors were also analyzed to assess independent risk factors for surgical site morbidity and unplanned reoperation in the first 30 postoperative days. Results: A total of 1, 592 PMFF were analyzed between 2007 and 2019. Of these, 2.7% (43/1592) developed a composite surgical site complication in the first 30 postoperative days. Risk factors for composite surgical site complication included >10% weight loss in the previous 6 months ( p <0.05), disseminated cancer ( p <0.01), class 4 wounds (dirty/infected) ( p <0.01), and operative time greater than 123 min ( p <0.01). Based on the univariate analysis, low preoperative albumin and hematocrit were also associated with increased odds of composite surgical site complication. 2.5% (40/1592) of patients underwent unplanned reoperation. Higher ASA class ( p <0.05) and class 4 wounds ( p <0.05) were associated with unplanned return to the operating room. Conclusion: Significant weight loss, disseminated cancer, prolonged operation time, low preoperative albumin, and hematocrit are associated with higher PMFF composite surgical site complications. Higher ASA and class 4 wound status are associated with an increased risk of unplanned reoperation.